Myanmar's human resources for health: current situation and its challenges. Issue 3 (March 2019) - Saw, Yu Mon; Than, Thet Mon; Thaung, Yamin; Aung, Sandar; Wen-Shuan Shiao, Laura; Win, Ei Mon; Khaing, Moe; Tun, Nyein Aye; Iriyama, Shigemi; Win, Hla Hla; Sakisaka, Kayako; Jimba, Masamine; et al.
Abstract: Background: Human resources for health (HRH) are the cornerstone of health systems, enabling the improvement of health service coverage. The systematic fortification of healthcare in Myanmar has accelerated since a new ruling party took office. Since 2006, Myanmar has been listed as one of the 57 crisis countries facing critical health workforce shortages. Therefore, this study aimed to assess the current situation of HRH in the public health sector where major healthcare services are provided to the people of Myanmar. Methods: A cross-sectional study was conducted from January to May 2017 by collecting secondary data from the official statistic of the Ministry of Health and Sports (MoHS), official reports, press-releases, and presentations of Government officials. The data were collected using a formatted excel spreadsheet. A descriptive analysis was applied and the density ratio per 1, 000 population for medical doctors and health workers was calculated. Findings: In total, 16, 292 medical doctors and 36, 054 nurses working at 1, 134 hospitals were under the management of MoHS in 2016. The finding revealed that 13 out of 15 States and Regions were below the WHO recommended minimum number of 1 per 1, 000 population for medical doctor. The distribution of medical doctors per 1, 000 population in the public sector showed a gradually decreasing trend since 2006. Urban and rural medical doctor ratios observed wide disparities. Interpretation: The HRH shortage occurred in almost all State and Regions of Myanmar, including major cities. Wide disparities of HRH were found in urban and rural areas. The Myanmar government needs to consider the proper cost-effective HRH supply-chain management systems and retention strategies. The projection of health workforce, distribution of workforce by equity, effective management, and health information systems should be strengthened.